Charging infrastructure demands of shared-use autonomous electric vehicles in urban areas - Zhang, Hongcai; Sheppard, Colin J.R.; Lipman, Timothy E.; Zeng, Teng; Moura, Scott J. (Transportation research. Part D, Transport and environment, 2020)
•Agent based simulation model to describe multi-model integrated transportation systems.•Siting and sizing charging stations subject to range and quality of service constraints.•Economic and environmental analysis of electrifying an autonomous electric vehicle fleet.•Investigation of the mutual effects between vehicle parameters and charging system parameters. Ride-hailing is a clear initial market for autonomous electric vehicles (AEVs) because it features high vehicle utilization levels and strong incentive to cut down labor costs. An extensive and reliable network of recharging infrastructure is the prerequisite to launch a lucrative AEV ride-hailing fleet. Hence, it is necessary to estimate the charging infrastructure demands for an AEV fleet in advance. This study proposes a charging system planning framework for a shared-use AEV fleet providing ride-hailing services in urban area. We first adopt an agent-based simulation model, called BEAM, to describe the complex behaviors of both passengers and transportation systems in urban cities. BEAM simulates the driving, parking and charging behaviors of the AEV fleet with range constraints and identifies times and locations of their charging demands. Then, based on BEAM simulation outputs, we adopt a hybrid algorithm to site and size charging stations to satisfy the charging demands subject to quality of service requirements. Based on the proposed framework, we estimate the charging infrastructure demands and calculate the corresponding economics and carbon emission impacts of electrifying a ride-hailing AEV fleet in the San Francisco Bay Area. We also investigate the impacts of various AEV and charging system parameters, e.g., fleet size, vehicle battery capacity and rated power of chargers, on the ride-hailing system’s overall costs.